2021
DOI: 10.3389/fnut.2020.603090
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Cues in Infant Feeds: Volatile Profiles of Different Milks Fed to Preterm Infants

Abstract: Background: Smell is determined by odor-active volatile compounds that bind to specific olfactory receptors, allowing us to discriminate different smells. Olfactory stimulation may assist with digestion and metabolism of feeds in the neonate by activation of the cephalic phase response of digestion. Infants' physiological responses to the smell of different milks suggest they can distinguish between breastmilk and infant formula. We aimed to describe the profile of volatile compounds in preterm breastmilk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 71 publications
4
11
1
Order By: Relevance
“…Previous studies suggested that the profile of volatile compounds in BM results from degradation of milk lipids (yielding ketones, aldehydes, alcohols, free FAs, and FAe) and from maternal diet (mostly terpenoids). 30 , 38 41 BM from ten mothers of FT infants was found to contain higher amounts of terpenes, aldehydes, and alcohols than infant formulas, 38 although, in contrast to our findings, that study only detected SCFA in the BM. However, samples analyzed in this study were all from mature BM (>5 weeks postnatal) provided by mothers of FT infants, which may explain the different results.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Previous studies suggested that the profile of volatile compounds in BM results from degradation of milk lipids (yielding ketones, aldehydes, alcohols, free FAs, and FAe) and from maternal diet (mostly terpenoids). 30 , 38 41 BM from ten mothers of FT infants was found to contain higher amounts of terpenes, aldehydes, and alcohols than infant formulas, 38 although, in contrast to our findings, that study only detected SCFA in the BM. However, samples analyzed in this study were all from mature BM (>5 weeks postnatal) provided by mothers of FT infants, which may explain the different results.…”
Section: Discussioncontrasting
confidence: 99%
“… 40 We previously reported that volatile compounds in 15 samples of preterm BM differed from those in infant formulas largely due to the presence of specific FA in BM that was absent from formulas. 30 Therefore, our findings are largely in agreement with previous reports and expand on the current knowledge of volatile compounds in BM by demonstrating that a variety of compounds of different chemical classes can be found in preterm BM, including MCFA and their esters, terpenoids, and VOCs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations